232 DETECTION OF POST STROKE DEPRESSION IN ACUTE STROKE UNIT AT UNIVERSITY HOSPITAL. (18th November 2021) - Mohamed, A; Wang, J; Gabr, A; Mustafa, W; O'Connor, M; Mulroy, M
Abstract: Background: Depression is the most common neuropsychiatric manifestation after stroke. It is associated with lower satisfaction and quality of life in stroke survivors and their families. Routine screening for mood disturbance is recommended in stroke patients Royal College of Physicians, 2016; National Office of Clinical Audit (NOCA) 2019. The psychological impact of a stroke can present challenges for assessment and diagnosis. We audited the assessment and diagnosis of post stroke depression in a teaching hospital. Methods: PHQ-9 was prospectively administered to stroke patients (and also to the next of kin with patient consent) within 2 weeks of stroke and repeated at 4–6 weeks after stroke in November 2016. The Patient Health Questionnaire (PHQ—9) is a self-administered, validated screening tool for depression. Chart diagnosis or drug prescribing for depression was retrospectively assessed in the medical and nursing notes. Results: 15 of 34 admitted stroke patients were administered the paper based PHQ-9. 19 patients were excluded due to: severe cognitive impairment; aphasic; death or having been discharged. No patient had depression diagnosed prior to admission to the hospital. One patient was diagnosed and prescribed an anti-depressant post stroke. 7 patients screened positive for depression on PHQ-9: mild depression n = 4 (27%); moderate n = 2 (13%); and severe depression n = 1 (6%). Repeat questionnaire at 4–6 weeks post stroke revealed an unchanged PHQ-9 score in n = 10 (67%); however n = 2 (11%) had deteriorated and n = 4 (22%) improved. Conclusion: Depression was a common finding in 47% of patients post stroke and was under-recognized without a formal screening process incorporated in clinical practice. A nuanced screening process, accounting for common co-morbidities such as aphasia and cognitive impairment, was incorporated after this audit. Further guidance is being developed by the National Stroke Programme based on NOCA feedback.